PENGELOLAAN PEMBELAJARAN DISCOVERY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA SISWA DI SEKOLAH DASAR - Sri Utaminingsih; Nanik Inayah; Naela Khusna Faela Shufa (Universitas Muria Kudus, 2021)
The purpose of this study is to describe the management of Discovery Learning onalternative energy materials to improve the high-level thinking skills of fourth gradestudents at SD Negeri Bintoro 5 Demak.The research method used is descriptive qualitative method. This research was conducted at SD Bintoro 5 Demak. This study used purposive sampling technique, the sample in this study was selected for class IV SD Bintoro 5 Demak. Data collection techniques used are tests, observations, interviews and documentation. The data analysis technique used quantitative descriptive analysis.The result of the research is that the management of Discovery Learning which consists of planning and implementation has been carried out according to the syntax, while the evaluation is done with tests. Furthermore, the results of children's higher-order thinking skills after participating in learning are very high. The percentage results on analytical skills are 84% in the very good category, the level of student understanding is 87% in the very good category, the problem solving ability is 72% in the good category, the ability to conclude is 86% in the very good category, and the ability to evaluate the findings by 75% with good category. The conclusion of this study is that learning management with the Discovery Learning model can improve students' higher order thinking skills.